Nilai Pendidikan Islam Dan Konsep Status Sosial Anak Perempuan Pada Upacara Kayik Nari Beterang Di Kabupaten Bengkulu Selatan - Pitaloka, Lola; Achadi, Muh. Wasith (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This study aims to determine what is the tradition of the kayik nari beterang ceremony, the perspective of Islamic educational values ??and the concept of social status of girls. Using qualitative methodology with an ethnographic approach, this study in Air Kemang Village, South Bengkulu Regency, the research subjects used purposive sampling techniques, namely village heads, traditional leaders, community leaders, midwives, parents of bunting kecik who carry out the kayik nari beterang ceremony tradition and their bunting kecik. Data collection techniques through observation, interviews, documentation, and data validity testing using triangulation. Data analysis techniques using the Spradley model with taxonomic analysis and domain analysis, the results of the study showed the tradition of the kayik nari beterang ceremony, a circumcision ceremony for girls aged 6 to 11 years, the process and stages of the kayik nari beterang ceremony tradition consist of four stages, namely first, the event party visits the midwife to determine the day and date of the event and record what tools and materials will be needed, second bathing, third dressing up and the fourth dancing or beterang. Then in the meaning of tools and materials from the side of Islamic Education values, there are three, namely the value of faith, moral values ??and Sharia values, and the concept of social status in the kayik nari beterang ceremony tradition is an intermediary for girls to get the title bunting kecik which marks a new role in their life in society, and they have completed carrying out the customary pillars.